Viral infection in thymoma and thymic tumors with autoimmune diseases. Issue 22 (17th September 2021) - Chang, Rui; Duan, Shuning; Li, Shicong; Zhang, Peng
Abstract: A thymoma is a type of thymic tumor which is rarely malignant that is frequently reported in adult patients. A number of thymoma‐related immune disorders are observed including autoimmune diseases, which suggests a strong connection between thymoma development and immunological mechanisms. Characterized by association with humoral and cellular immunodeficiency, thymoma patients are susceptible to opportunistic infections by environmental factors. Recent reports have suggested that viral infection may play a role in the etiological mechanisms of thymoma development associated with dysregulated immunity. In this review, we summarize the case reports and studies related to viral infection, such as CMV, EBV and HSV, that probably play a part in the pathogenesis of thymoma and related diseases. Furthermore, we demonstrate the underlying mechanisms by which viruses may induce the occurrence of thymoma with autoimmune diseases. Lastly, we discuss the potential application of antiviral therapy in the treatment of thymic diseases.